SUMBANGAN TEKNIK INFORMATIKA DALAM MEWUJUDKAN SEKOLAH EFEKTIF - Lantip Diat Prasojo (MAJALAH ILMIAH PEMBELAJARAN, 2006)
The growth of information technology had followed by a school so that can face the global emulation. Information technology gave the contribution which enough mean in realizing effective school like: in the field of study, school publication, School leadership, school administration. Implementation of information technology in a school very assisting like: exploiting internet, LAN (Local Area Network), multimedia, e-learning, mailing list, and others.Effective school is a success school it’s meaning an institute of education organizer which have owned the good independence so that can upgrade the education. Effective school characteristic cover three elements, that is: input, process, and output which are the each element elaborated to become some characteristic. Effective school more focused at independence owned so that can challenge and always developed of self in order to reaching its target.